Film Thinckness effect on Structure and Optical Properties of nanostructured ZnS thin films Deposited By spray Technique - Ayadi, M.; Benhaoua, A.; Benramache, S.; Sebais, M.; Halimi, O.; Boudine, B. (University of Eloued جامعة الوادي, 2019)
In this work, the sprayed ZnS thin films were deposited on glass substrate at 400C° using ultrasonic spray chemical technique (SPC). The effect of film thickness on structure and optical properties of nanostructured ZnS thin films was investigated. From XRD analysis, it was observed that the prepared material has a hexagonal structure with good crystallinity. This finding was in a good agreement with the morphological properties in the SEM images. It was also found that the maximum crystallite size is 45.3nm, which was obtainedwith577 nm film thickness. From optically experiments, ZnS thin films have a good transparency in visible region and the band gap energy of all deposit films was varied in the range 3.9-4.1eV في هدا العمل قمنا بتحضير الأغشية الرقيقة لكبريتات الزنك مرسبة على حوامل الزجاج عند درجة مئوية 400 بواسطة تقنية الرش و تمت دراسة تأثير السمك على الخواص البنيوية و الضوئية لهده الأغشية. بينت نتائج الأشعة السينيةأن المادة المحضرة ذات تبلور جيد وتملك بنية سداسية،وهده الأخيرة في توافق جيد مع نتائج الماسح الإلكتروني. و قد وجد أن الحجم الأعظمي للحبيبات هو 45.3نانو متر للعينة ذات السمك 577نانو متر. فيما يخص الدراسة الضوئية بينت النتائج أن الأغشية ذات شفافية جيدة في المجال المرئي وأن قيمة الفاصل الطاقي تتغير ما بين 3.9 و4.1
الندوة الدولية الرابعة حول المواد و التنمية المستدامة علوم التكنولوجيا تاريخ انعقاد الملتقى: 12-14نوفمبر 2019 جامعة بومرداس
Keywords: ZnS; thin films; film thickness; ultrasonic spray method; كبريتات الزنك, الأغشية الرقيقة ,سمك الغشاء, تقنية الرش باستعمال الأمواج الفوق الصوتية